Psychological and Pedagogical Principles of Development of Communicative Competence of Future Journalists Based on Linguoculturology - Nataliya Yu. Kondratenko; Hanna V. Marchenko; Svitlana O. Stezhko (Mukachevo State University, 2021)
The relevance of the study is conditioned by the active development of socio-cultural factors that require qualitatively new requirements for the development of professional competences, including communicative competence of future journalists, taking into account psychological and pedagogical conditions. The purpose of the study is to determine and substantiate the psychological and pedagogical principles in the process of developing the communicative competence of future journalists based on linguocultural studies. The study of the selected issues was based on a system-structural approach using methods of analysis, synthesis, comparison, as well as the method of rising from abstract to concrete. The urgency of the development of communicative competence in the field of humanities has been identified, in accordance with which the opinions on the interpretation of this concept have been investigated. The study defined the communicative competence of future journalists. The necessity of developing communicative competence based on linguoculturology has been clarified. The main psychological and pedagogical principles of development of communicative competence of future journalists are described, which include motivation, professional interest, development of communication skills and maintenance of the level of all types of speech activity. A list of examples of practical tasks to improve the communicative competence of future journalists, which should be used by teachers in teaching certain disciplines, is proposed and substantiated. It was found that the creative component of communicative competence is the key to successful professional growth of every future specialist in the field of journalism. Prospects for further research are focused on empirical proof of the use of the described methods of developing professional competencies of future journalists